PENGARUH FAKTOR WORKING CAPITAL TERHADAP FIRM PERFORMANCE DIMODERASI OLEH WORKING CAPITAL REQUIREMENT - Wijaya, Agustina; Imelda, Elsa (Jurnal Paradigma Akuntansi, 2024)
The research was conducted with the aim to find the effect of firm age, cash flow, firm size, leverage, and sales growth on firm performance with net liquid balance as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The sample in this study was 252 companies data obtained through purposive sampling method. The data processing process used the EViews 12 application and Microsoft Excel 2019. This study obtained the results that cash flow, firm age, sales growth, and leverage have a significant effect on firm performance. While firm size does not affect firm performance. The study also shows that WCR is only able to moderate the effect of firm age, cash flow, leverage, and firm size on firm performance. The implication of this research is that management must regulate and maintain the company's WCR level to create maximum company performance.